Effect of Aging on the Macrophage Response to Titanium Particles - Jämsen, Eemeli (J Orthop Res, 2019)
Macrophage-mediated inflammatory reaction to implant wear particles drives bone loss around total joint replacements (TJR). Although most TJR recipients are elderly, studies linking wear particle-activated macrophages and peri-implant osteolysis have not taken into account the multiple effects that aging has on the innate immune system and, in particular, on macrophages. To address this, we compared the wear particle responses of bone marrow macrophages obtained from young (2-month) and aged (18-month) mice. Macrophages were polarized to M0, M1, or M2 phenotypes in vitro, challenged with titanium particles, and their inflammatory response was characterized at multiple time points by qRT-PCR and ELISA. In addition, age-dependent changes in activation of transcription factor NF-κB were analyzed by a lentiviral vector-based luciferase reporter system. The particle stimulation experiment was further repeated using human primary macrophages isolated from blood donors of different ages. We found that the pro-inflammatory responses were generally higher in macrophages obtained from young mice, but differences between the age groups remained small and of uncertain biological significance. Noteworthily, M2 polarization effectively suppressed the particle-induced inflammation in both young and aged macrophages. These results suggest that aging of the innate immune system per se plays no significant role in the response of macrophages to titanium particles, whereas induction of M2 polarization appears a promising strategy to limit macrophage-mediated inflammation regardless of age.